Sn-Cu intermetallic compound laminated film with excellent friction coefficient, contact resistance, and solder wettability. (2nd January 2022) - Hayashi, Hiroki; Takaine, Naohiro; Funasaki, Hiroyuki; Watanabe, Mitsuhiro
ABSTRACT: The connector used for electronic parts of automobiles is a type with Sn plating on the copper surface. In recent years, as the number of connector pins has increased and the insertion force has increased, problems have arisen in the insertion and removal operations. In addition, the reliability of the connection in high temperature environments needs to be improved. Various Sn plating alternative processes have been developed to meet these demands. Tha authors have previously reported on Sn-Cu plating processes that can provide more stable properties. 1 Using Sn-Cu plating and Sn plating, a Cu6 Sn5 intermetallic compound layer with low roughness formed just below the surface. A pure Sn layer is formed on it. The authors have previously reported that the formation of a pure Sn layer with high connection reliability and a stable hard intermetallic compound layer can be expected to improve various properties. In this study, as a result of investigating the solder wettability of this plating film, which has excellent low friction coefficient and low contact resistance, it was clarified that good connector characteristics can be obtained.